1968
DOI: 10.1007/bf02667106
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis and calorimetry of some fatty acid sodium soaps

Abstract: Transition temperatures and enthalpies and some phase diagrams of pure odd and even sodium soaps have been determined by means of differential thermal analysis and scanning calorimetry. Branched sodium soaps have been added for comparison.No essential difference has been found between the number, type, and enthalpy of the transitions of the neighboring odd and even soaps. The total enthalpy and entropy of transition are considerably lower than those of the corresponding paraffins and fatty acids. The entropy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

1969
1969
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 13 publications
2
17
1
Order By: Relevance
“…The thermograms obtained under these conditions are consistent with those of Pacor and £pier (10), and reported on the fig. 3, which shows for comparison the thermograms of the anhydrous sodium laurate and myristate.…”
Section: The Anhydrous Soapssupporting
confidence: 90%
“…The thermograms obtained under these conditions are consistent with those of Pacor and £pier (10), and reported on the fig. 3, which shows for comparison the thermograms of the anhydrous sodium laurate and myristate.…”
Section: The Anhydrous Soapssupporting
confidence: 90%
“…Thereby, T dec values increase linearly by 1.9°C per additional CH 2 group. Common alkali soaps are thermally more stable (over 350°C), 26,36À39 while other monoanionic surfactants such as sodium dodecyl sulfate (T dec = 222°C) 40 The Journal of Physical Chemistry B ARTICLE somehow slightly lower than expected on the basis of our experiments. Discrepancies might originate from different heating rates.…”
Section: ' Introductioncontrasting
confidence: 46%
“…When heated through a temperature range of 20–160°C (i.e. the range under study here), two principle transitions are observed at 125.9°C and 133.7°C for sodium stearate and 123.0°C and 136.1°C for sodium palmitate respectively, these two transitions corresponding to the curd‐subwaxy phase transition and subwaxy‐waxy phase transition of the fatty acid salts, respectively 25…”
Section: Resultsmentioning
confidence: 99%